MUI’s fatwa on interfaith greetings and religious tolerance: can Indonesia find a middle ground? - Dharta, Firdaus Yuni; Susanto, Tri; Anggara, Reddy; Hariyanto, Fajar; Sianturi, Hendry Roris P. (Frontiers in Communication, 2025)
This perspective article examines the ongoing debate surrounding the Indonesian Ulema Council’s (MUI) fatwa on interfaith greetings, highlighting tensions between religious purity and social tolerance in Indonesia’s pluralistic society. It traces MUI’s position from its 1981 fatwa prohibiting greetings such as Assalamu’alaikum, Shalom, Om Swastiastu, Namo Buddhaya, and Salam Kebajikan to continued discussions in the 2000s and 2020s. The Ministry of Religion (Kemenag) has promoted religious moderation as a means to balance religious diversity and national unity, presenting an alternative stance to MUI’s prohibitive approach. Using Ting-Toomey’s Negotiated Identity Theory, this article explores how religious identity is shaped by social interactions and adaptation within multicultural settings. The negotiation of religious identity in Indonesia is particularly complex, as religious groups must reconcile theological principles with the realities of coexistence. The article emphasizes the need for open dialogue and collaboration between religious communities to foster mutual understanding. While some perspectives strictly adhere to MUI’s fatwa, others advocate for contextual consideration, recognizing the influence of diverse cultural and educational backgrounds. The discussion highlights differing interpretations of religious teachings and the socio-political dynamics that shape this discourse. Ultimately, this article advocates for a balanced approach—one that respects religious traditions while fostering social cohesion. By promoting inclusivity and mutual respect, Indonesia can cultivate a harmonious society where interfaith relationships are nurtured, ensuring that diversity becomes a source of unity rather than division.